Productive Zakat and Distribution Strategies in Improving the Welfare of Mustahik at LAZ DT. Peduli North Sumatera - Dani, Rama (Program Studi Manajemen Zakat dan Wakaf, 2025)
The distribution of zakat does not only emphasize distribution strategy as consumptive, but also emphasizes more effective and productive distribution strategies. The productive zakat distribution strategy is an effort to improve the welfare of mustahik. This study aims to describe the distribution strategy of productive zakat and the effect of the distributions on the welfare of mustahik. This research was describes the zakat distribution strategy and the impact of distribution on the welfare of the mustahik. The research was conducted at the LAZ DT Peduli North Sumatra, is a type of descriptive qualitative research with testing procedures that are carried out in depth using purposive testing procedures. The procedure for the validity of information uses triangulation. Data analysis in this study uses reduction, data presentation, and conclusion drawn. The test of this research is mustahik who is the beneficiary of Profitable Zakat. Sources of information obtained from program management and staff's and profitable zakat in LAZ DT Peduli North Sumatra. The result showed that the effect of profitable zakat dispersion technique on the level of mustahik welfare is very critical. Based on the level of welfare of mustahik, beneficial zakat mustahik have been able to meet daily needs, have a permanent job, can get wellbeing offices, have a better than average put to live, the normal mustahik's wage has expanded by 63.38% and has been able to create a sustainable business.